Evaluating cognitive performance using virtual reality gamified exercises - Borghetti, Davide; Zanobini, Carlotta; Natola, Ilenia; Ottino, Saverio; Parenti, Angela; Brugada-Ramentol, Victòria; Jalali, Hossein; Bozorgzadeh, Amir (Frontiers in Virtual Reality, 2023)
Virtual Reality (VR) environments have been proven useful in memory assessment and have shown to be more sensitive than pen-and-paper in prospective memory assessment. Moreover, these techniques provide the advantage of offering neuropsychological evaluations in a controlled, ecologically valid, and safe manner. In the present study, we used Enhance VR, a cognitive training and assessment tool in virtual reality. User performance was evaluated by means of the in-game scoring system. The primary goal of this study was to compare Enhance VR in-game scoring to already existing validated cognitive assessment tests. As a secondary goal, we tested the tolerance and usability of the system. 41 older adults took part in the study (mean age = 62.8 years). Each participant was evaluated with a predefined set of traditional pen-and-paper cognitive assessment tools and played four VR games. We failed to find a significant positive impact in explaining the variability of the Enhance VR game scores by the traditional pen-and-paper methodologies that addressed the same cognitive ability. This lack of effect may be related to the gamified environment of Enhance VR, where the players are awarded or subtracted points depending on their game performance, thus deviating from the scoring system used in traditional methodologies. Moreover, while the games were inspired by traditional assessment methodologies, presenting them in a VR environment might modify the processing of the information provided to the participant. The hardware and Enhance VR games were extremely well tolerated, intuitive, and within the reach of even those with no experience.